2016
DOI: 10.1155/2016/7874084
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Features of Pediatric Ocular Trauma in Egypt

Abstract: Purpose. To review the epidemiology of serious pediatric ocular trauma presenting to Kasr El Aini Hospital, Cairo University. Methods. Children with serious ocular trauma during a six-month period were examined and their data was analyzed. Results. Eighty eyes of 75 patients were included in this study, with 64% males (P < 0.001) and average age of 5 years (5 months–15 years). There were 67 (83.75%) open globe injuries, 11 (13.75%) closed globe injuries, and 2 (2.5%) chemical injuries. Of the open globe injuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 37 publications
(51 reference statements)
7
23
2
Order By: Relevance
“…Studies have quoted percentage of males affected are more than the females. 3,11,13,22,23,[25][26][27] Our study also showed preponderance to males 38 (62.3%) over females 23 (37.7%). A possible reason for this finding could be that boys are more involved than females in outdoor activities.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Studies have quoted percentage of males affected are more than the females. 3,11,13,22,23,[25][26][27] Our study also showed preponderance to males 38 (62.3%) over females 23 (37.7%). A possible reason for this finding could be that boys are more involved than females in outdoor activities.…”
Section: Discussionsupporting
confidence: 67%
“…21 Wadeai et al noted an increase in the childhood trauma to the extent of 49.7% in the Egyptian population. 22 In the Nigerian population, the proportion of eye injuries in children was 26.4%. 15 A study from an Arabian country demonstrated a high incidence of pediatric trauma to the tune of 58.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In young children, ocular trauma is one of the major threats of monocular blindness [1][2][3][4]. It was reported that the incidence of severe visual impairment or blindness caused by ocular trauma ranged from 2% to 14% in young children [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Pars plana vitrectomy (PPV) is a major surgical intervention which has been used to manage severely damaged eyes [9]. Some studies have reported the epidemiological features of pediatric ocular trauma in developing countries, including India [10,11], Egypt [1] and Turkey [7]. However, quite few studies described the clinical characteristics and outcomes of PPV in pediatric ocular trauma.…”
Section: Introductionmentioning
confidence: 99%